Basic principles in physical chemistry (TYBSc) - Raghuraman K., Prabhu D.V., Sathe P.A. and others (Sheth Publ., Mumbai, 2004)
Chemistry
ENGLISH
Keywords: Basic principles in physical chemistry (TYBSc); Chemistry; Chemistry